Magnetic resonance imaging in the preoperative staging of endometrial carcinoma - Cabrita, S (2008)
PURPOSE OF INVESTIGATION: Magnetic resonance imaging (MRI) has emerged as an important imaging modality in the evaluation of the extension of endometrial carcinoma which is essential in planning treatment and predicting prognosis. This study aimed to assess the value of MRI in the preoperative staging of endometrial carcinoma. METHODS: We included in this study 162 patients with a histological diagnosis of endometrial carcinoma who underwent MRI pelvic imaging and surgical staging. MRI images were compared with pathological findings to measure MRI's sensitivity, specificity, positive and negative predictive values and diagnostic accuracy in what concerns myometrial, cervical and lymph node invasion. RESULTS: MRI differentiation of deep myometrial invasion from superficial disease agreed with pathological findings in 77% of cases, with a sensitivity of 83%, a specificity of 72% and a diagnostic accuracy of 77%. Concerning cervical invasion, MRI had a sensitivity, specificity and diagnostic accuracy of 42%, 92%, 81% respectively. In assessing lymph node invasion, MRI presented a sensitivity of just 17%, a specificity of 99% and a diagnostic accuracy of 89%. CONCLUSION: Our study confirmed the high accuracy of MRI imaging in assessing myometrial and cervical invasion in endometrial carcinoma. When evaluating lymph node invasion, micrometastases are responsible for the low sensitivy of MRI.